The Influence of Work Motivation and Job Satisfaction from an Islamic Economic Perspective on Employee Performance at PT BPRS Hikmah Bahari Head Office Tegal - Diana Khristina; Widodo (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to analyze the effect of work motivation on job satisfaction and employee performance, as well as the effect of job satisfaction on employee performance at PT. BPRS Hikmah Bahari Head Office. This research uses a quantitative approach with a causal design. Data were collected through questionnaires distributed to 47 respondents using a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 4. The results show that work motivation has a positive and significant effect on job satisfaction and employee performance. Job satisfaction also has a significant effect on employee performance. The R-square value indicates that job satisfaction is influenced by work motivation by 78.9%, while employee performance is influenced by work motivation and job satisfaction by 85..6%.